APLIKASI PEMBANGKIT PWM UNTUK MENGENDALIKAN KIPAS PADA DESKTOP KOMPUTER BERBASIS MIKROKONTROLER ATMEGA 8535 K - esrawati siregar (Saintia Fisika, 2013)
Has been designed and realized PWM Generator Application for controlling Fan on Desktop computer based Microcontroller ATMega8535. With the automatic control system that work to keep the electronic component from overheating problem. Temperature control system governed by the PWM signal. Therefore the PWM signal will be generated by controlling the pulse width of the PWM signal (Ton) and temperature values are referenced from the input keypad. Moreover the system is designed and equipped with a temperature sensor LM35 each of which is installed in the PSA, RAM and Processor which will be used to detect any changes in temperature that occur in each individual sensor and temperature sensor value changes and the resulting pulse width will be displayed to the LCD. Keyword : PWM, , LM35, controlling Fan